Hepatitis B, C, and D Virus Infections and AFP Tumor Marker Prevalence Among the Elderly Population in Mongolia: A Nationwide Survey - Davaalkham Dambadarjaa; Yerkyebulan Mukhtar; Enkh-Oyun Tsogzolbaatar; Ser-Od Khuyag; Angarmurun Dayan; Nandin-Erdene Oyunbileg; Oyu-Erdene Shagdarsuren; Gunchmaa Nyam; Yosikazu Nakamura; Masaharu Takahashi; Hiroaki Okamoto (Korean Society for Preventive Medicine, 2022)
Objectives Infections with hepatitis B, C, and D virus (HBV, HCV, and HDV) are a major public health problem and lead to serious complications such as cirrhosis and hepatocellular carcinoma. We aimed to determine the seroprevalence of hepatitis B surface antigen (HBsAg), anti-HCV, anti-HDV immunoglobulin G, alpha-fetoprotein (AFP), and dual and triple hepatitis virus infections in Mongolia. Methods A total of 2313 participants from urban and rural regions were randomly recruited for this cross-sectional study. A questionnaire was used to identify the risk factors for hepatitis virus infections, and the seromarkers were measured using immunoassay kits. Results Among all participants, the prevalence of HBV, HCV, and HDV was 15.6%, 36.6%, and 14.3%, respectively. The infection rates were significantly higher in females and participants with a lower education level, rural residence, older age, and a history of blood transfusion. HBV and HCV co-infection was found in 120 (5.2%) participants and HBV, HCV, and HDV triple infection was detected in 67 (2.9%) participants. The prevalence of elevated AFP was 2.7%, 5.5%, and 2.6% higher in participants who were seropositive for HBsAg (p=0.01), anti-HCV (p<0.001), and anti-HDV (p=0.022), respectively. Elevated AFP was more prevalent in participants co-infected with HBV and HCV (5.8%, p=0.023), HBV and HDV (6.0%, p<0.001), and triple-infected with HBV, HCV, and HDV (7.5%) than in uninfected individuals. Conclusions Nearly half (49.8%) of the study population aged ≥40 years were infected with HBV, HCV, or HDV, and 22.4% had dual or triple infections.